The linear electromagnetic gyrokinetic global simulation by using the numerical Lie-transform code - Guodong Zhang; Jinxiang You; Zihao Wang; Tiannan Wu; Yuefeng Qiu; Lu Wang; Shaojie Wang (AIP Advances)
Electromagnetic gyrokinetic simulation plays an important role in the research of anomalous transport driven by micro-turbulence in tokamak fusion plasmas. The development of electromagnetic gyrokinetic codes usually faces challenges including physical model, numerical instabilities as well as corresponding algorithms and accuracy; one of the typical challenges is the well-known cancellation problem. In this work, the gyrokinetic code NLT [Ye et al., J. Comput. Phys. 316, 180 (2016)] is updated to the electromagnetic version. The scheme of mitigating the cancellation problem in GYRO [Candy and Waltz, J. Comput. Phys. 186, 545 (2003)] is adopted. The simulation results including the real frequency, linear growth rate, and mode structures of the ion temperature gradient mode and the trapped electron mode as well as the kinetic ballooning mode from NLT are consistent with those from previous Eulerian and particle in cell codes. Moreover, it is found that the cancellation problem does not exist, at least for the drift waves, in the NLT simulation.